Minibeam Radiation Therapy for Recurrent Mucosal Melanoma: An Eye-Opening Response - Maddi A. Jacobson, MPAS, PA-C; Yasamin Sharifzadeh, MD; Arkadiusz Z. Dudek, MD, PhD; Svetomir N. Markovic, MD, PhD; Jeffrey E. Johnson, MD; Jonathan M. Morris, MD; Scott C. Lester, MD; Robert W. Mutter, MD; Michael P. Grams, PhD; Sean S. Park, MD, PhD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes)
We report a case of novel radiation treatment referred to as minibeam radiation therapy (MBRT) that was used to treat recurrent mucosal melanoma. The patient’s disease recurred after surgery, conventional radiation therapy, and 4 lines of systemic therapy, and then, the patient was referred to our clinic. Despite substantial disease progression after multiple prior therapies, a complete metabolic and clinical response, along with an improved quality of life and performance status, was achieved after 2 treatments of MBRT. Additionally, disease response was noted in an unirradiated abdominal metastasis. The MBRT treatments were well-tolerated, with minimal toxicity reported more than 6 months posttreatment. This case highlights the potential of MBRT as a completely novel form of radiation therapy that warrants further study.